Herptile Website Resources - Forrester, Harriet; Hale, Lorrie (Wildlife Rehabilitation Bulletin, 2006)
The following websites have been useful to the authors and contain a wide variety of information on various species of herpetiles. These resources can be invaluable to rehabilitators receiving a new species or seeking additional information on one more familiar.